The Battleground of Everyday Life: Balancing Motherhood and Career as a Danish Soldier's Partner - Maj Hedegaard Heiselberg (The Royal Danish Library, 2018)
Based on ethnographic fieldwork among Danish soldiers and their families, this article focuses on soldiers’ partners’ experiences of military deployment. The aim is to provide an understanding of the social consequences of deployment that goes beyond the scope of a specific military culture and into the intimate world of family relations. The article argues that examining the effects of military deployment on the homefront requires attention to the local and social context in which soldiers’ families live their everyday lives. In a Danish context, military deployment not only disrupts normal routines of everyday family life but causes an imbalance in the ‘moral economy of home’. From the perspective of soldiers’ partners, deployment challenges ideals of equal opportunity among partners outside the domestic sphere of home by preventing the women from pursuing their own careers and social engagements. Moreover, the absence of a parent challenges ideals of parenthood as a shared responsibility belonging to both parents, and consequently places the women in a precarious situation, where they continuously struggle to balance their time and social roles in and outside the home.